2005
DOI: 10.1016/j.jacc.2005.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Left Ventricular Assist Device Therapy on Ventricular Arrhythmias

Abstract: After LVAD placement, there is a significant rise in the incidence of de novo MVT. By contrast, the incidence of PVT/VF was unaffected by LVAD placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
177
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(189 citation statements)
references
References 12 publications
9
177
1
2
Order By: Relevance
“…6 Similar findings have been seen in single-center observational studies, where VA have been reported to occur in 22% to 59% of LVAD recipients (Table). 6,[10][11][12][13][14][15][16][17][18] Incident VAs are also seen in patients who have not had VA before LVAD implant. Ziv et al 14 retrospectively studied 91 consecutive patients who underwent implant of a firstgeneration Heartmate XVE device.…”
Section: Epidemiologymentioning
confidence: 99%
“…6 Similar findings have been seen in single-center observational studies, where VA have been reported to occur in 22% to 59% of LVAD recipients (Table). 6,[10][11][12][13][14][15][16][17][18] Incident VAs are also seen in patients who have not had VA before LVAD implant. Ziv et al 14 retrospectively studied 91 consecutive patients who underwent implant of a firstgeneration Heartmate XVE device.…”
Section: Epidemiologymentioning
confidence: 99%
“…6 An early postoperative period study after cardiac unloading therapy in 17 HF patients showed that in the first two weeks after LVAD implantation, HF was associated with a relatively high incidence of ventricular arrhythmias associated with QTc interval prolongation 7 . In addition, a recent retrospective study of 100 adult patients with advanced HF, treated with an axial-flow HeartMate LVAD suggested that the rate of new-onset monomorphic ventricular tachycardia (MVT) was increased in LVADtreated patients compared to patients given only medical treatment, while no effect was observed on the development of polymorphic ventricular tachycardia (PVT)/ventricular fibrillation (VF) 8 .…”
mentioning
confidence: 99%
“…Por otro lado, las infecciones relacionadas a dispositivos son frecuentes, con una incidencia cercana a 50% 16,17 . También se ha descrito una mayor incidencia de taquicardia ventricular monomorfa, especialmente en la primera semana posimplante 18 .…”
Section: Discussionunclassified